A new species of Larsia Fittkau, 1962 (Diptera: Chironomidae: Tanypodinae) from phytotelmata of Aechmea distichantha Lemaire, 1853 (Bromeliaceae) in Argentina - Siri, Augusto (2014)
A new species of Larsia Fittkau, 1962, viz. Larsia angusticornis sp. n., is described and adults and immatures are figured. The study is based on larvae collected from phytotelmata of the bromeliad Aechmea distichantha Lemaire, 1853 in northeastern Argentina that were reared to the adult stage. The pupa bears thoracic horns unusual for the genus, which distinguish this new species from other Larsia species.